2021
DOI: 10.1007/s00592-021-01707-9
|View full text |Cite|
|
Sign up to set email alerts
|

Screening of postpartum diabetes in women with gestational diabetes: high-risk subgroups and areas for improvements—the STRONG observational study

Abstract: Aims To assess the proportion of women with gestational diabetes (GDM) by performing postpartum Oral Glucose Tolerance Test (OGTT) and to identify GDM phenotypes at high-risk of postpartum dysglycemia (PPD). Methods Observational, retrospective, multicenter study involving consecutive GDM women. Recursive partitioning (RECPAM) analysis was used to identify distinct and homogeneous subgroups of women at different PPD risk. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…In addition, there seem to be limited evidence to compare the prevalence of T2DM post-GDM in different ethnicities including PIMA Indians. A recent study by Napoli et al [ 25 ] in Italy, reported that only 34.4% of women from ‘STRONG’ observational study underwent postpartum glucose monitoring. We also observed that only three studies had a follow-up rate of more than 70%, although we have showed earlier that it is feasible at least in research settings, with a follow up of 95.8% [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there seem to be limited evidence to compare the prevalence of T2DM post-GDM in different ethnicities including PIMA Indians. A recent study by Napoli et al [ 25 ] in Italy, reported that only 34.4% of women from ‘STRONG’ observational study underwent postpartum glucose monitoring. We also observed that only three studies had a follow-up rate of more than 70%, although we have showed earlier that it is feasible at least in research settings, with a follow up of 95.8% [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“… 13 In addition to the reasons associated with clinicians and healthcare system, the mothers’ paucity of time to perform the glucose test and lack of knowledge that they are at higher risks of postpartum dysglycemia aggravate the poor uptake rate of follow-up after delivery. 30 31 Therefore, it may be more ideal and feasible, at an antepartum stage, to educate women with GDM about their future risk for T2DM to enhance their healthcare awareness and health management. On the other hand, early risk stratification spares low-risk patients from unnecessary medical care while ensuring knowledge of diabetes and preventative interventions are delivered adequately to women in high-risk categories.…”
Section: Discussionmentioning
confidence: 99%
“…Even in active care, the average follow-up rate was still relatively modest at 64.8% 13. In addition to the reasons associated with clinicians and healthcare system, the mothers’ paucity of time to perform the glucose test and lack of knowledge that they are at higher risks of postpartum dysglycemia aggravate the poor uptake rate of follow-up after delivery 30 31. Therefore, it may be more ideal and feasible, at an antepartum stage, to educate women with GDM about their future risk for T2DM to enhance their healthcare awareness and health management.…”
Section: Discussionmentioning
confidence: 99%
“…Previously reported prevalence of persisting dysglycaemia in women following GDM affected pregnancy is found to vary, with 23% reported within 12 weeks from delivery in Italy,[20] 40% within 7 months post-partum in South Asia and even up to 48% at a median of 20 months post-partum in India. [21] The most recent estimates of persisting dysglycaemia in the Australian population was reported in 2021, with 22% of First Nation women but no Caucasian women developing T2DM following GDM at a median of 2.5 years follow-up.…”
Section: Discussionmentioning
confidence: 99%